Sistem Pendukung Keputusan Penentuan Penerima Beasiswa Cendikia Baznas(BCB)Kota Dumai Menggunakan Metode Combined Compromise Solution (CoCoSo) - Sarah Zulvianty; Tri Handayani; Ari Sellyana (Jurnal Teknologi Komputer dan Informasi, 2024)
The National Zakat Amil Agency (BAZNAS) is an official body formed by the government based on the Decree of the President of the Republic of Indonesia which has the task and function of collecting and distributing zakat, infaq and alms at the national level. The Cendikia Baznas Scholarship (BCB) Dumai City is one of the Dumai Smart programs which is intended for prospective and underprivileged students from Dumai City who will study at the Tazkia Bogor Islamic Institute (IAI) with all costs borne by Baznas Dumai City. Dumai City Baznas always provides BCB scholarships with a quota of five people who will be selected to undertake 4 years of education at IAI Tazkia Bogor. The selection of BCB scholarship recipients is based on several criteria such as grade transcripts, parents' income, registration form, parental approval letter, achievements, school recommendation letters, certificates of incapacity, participation in organizations, academic tests, and writing the essay "Me in 2030 ”. These criteria will show their eligibility as a BCB scholarship recipient. Currently, there is no computerized calculation process that uses unclear decision-making methods and reporting processes in selecting the BCB scholarship, so it is considered inappropriate. Therefore, we need a system using the CoCoSo method to rank the names of prospective students who will be selected as BCB Dumai City scholarship recipients, with the final result being alternative A37 in the name of Elli Suryati which has the highest optimization value, namely 1.4593, which is the best alternative. Becoming a BCB scholarship recipient is followed by the next four alternatives, namely alternative A44 with the name Bayu Alfi Putra, Alternative A38 named Deswandi Saputra, Alternative A23 named Naufal Hakim, and Alternative A25 named Van Halen.